T. F. Torrance on Scripture - Webster, John (Scottish journal of theology, 2012)
Although it was never completed and has had only slight impact, T. F. Torrance's work on the nature and interpretation of scripture is a primary element in his theology, though largely unstudied. For Torrance, a theology of scripture and its interpretation derive from a theology of revelation; revelation takes creaturely form in the incarnate Word, out of which is generated the apostolic community and its witness, which in turn generates scripture, the human word which ministers the divine Word. Scripture is the divine Word accommodated to human form, and so a sacrament or sign which refers to revelation; its social location is the life of the apostolic community. Interpretation of scripture is properly ‘depth-interpretation’, following the semantics of scripture by which reference to divine reality is made, rather than terminating on scripture's syntactical surface. Fitting interpretative practice follows the text's reference, penetrates to the thing signified, indwells its subject matters and listens to the divine Word. The interpreter is summoned to mortification of prejudice and constantly renewed attentiveness. Torrance's most impressive contribution to bibliology and hermeneutics was his insistence that both are ingredients within a theology of God's economic presence. There are some historical limitations to his work, along with a lack of interest in the Christian literary culture and lack of extended exegesis. However, his writings in the field constitute one of the most impressive Protestant accounts of the field in the last half-century.